COMPETENCIES APPROACH OF TEACHING INFORMATION SYSTEMS AND TECHNOLOGY OF THE FUTURE TEACHERS OF ECONOMICS - Kuzmina, Н.М.; Strutynska, О.В. (Journal of Information Technologies in Education (ITE), 2011)
The Article is dedicated to possibility of the use competencies approach in process of the education information system and technology of the future teachers of the economics. It is thus suggested to use an educational information environment that includes the distance course 'Information systems and technology in the economy' and pedagogical software program 'Financial analysis and optimization' that has been designed by the authors of teaching information systems and technologies to future teachers of economics. During work in such educational information environment, students of economics specialities of pedagogical universities not only acquire competencies of the education information systems and technology in the economy but also professionally pedagogical competencies.